Deep eutectic solvent coupled with high performance liquid chromatography for extraction of bisphenols and phthalates from selected freshwater source in Selangor, Malaysia - Jananee Balaraman,; Noorashikin Md Saleh,; Muhammad Zulhaziman Mat Salleh,; Farhanini Yusoff,; Saliza Asman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bisphenol A (BPA) and phthalates (PAEs) are endocrine disrupting chemicals that are abundantly found in the environment. These chemicals leach from polycarbonate plastics and epoxy resins into the environment when exposed to heat. Human exposure to these chemicals causes various health issues; hence, the detection of BPA and PAEs has become more sensitive, and thus it is the most important environmental issue to be reduced due to consequences on human health. This research aimed to determine the optimum parameter of extraction process for BPA and PAEs from water samples by using deep eutectic solvent (DES) coupled with high performance liquid chromatography- ultraviolet spectroscopy (HPLC-UV). Water samples for BPA and PAEs extraction were from various rivers and lakes in Selangor. The solvent used in the DES was a mixture of decanoic acid and tetrabutylammonium iodide. The extraction parameters that have been studied are molar ratio i.e., 1:2, 1:3 and 1:4, extraction time i.e., 10, 15 and 20 min, extraction temperature i.e., 50, 60 and 70 ºC and solvent volume i.e., 3, 6 and 9 mL. The optimum molar ratio of solvent and extraction time were 1:2 and 20 min, respectively. The best extraction temperature and volume of solvent with the highest recovery rate were 70 ºC and 3 mL. Sungai Kuang shows the highest bisphenol-A concentration of 23.9613 μg/L while Sungai Nada has the highest benzyl-butyl phthalates concentration of 73.6834 μg/L. Sungai Damansara shows the highest dibutyl phthalates concentration of 7.3163 μg/L. In conclusion, data obtained in this research will contribute a new knowledge in the Sustainable Development Goals 6, which is clean water and sanitation because the world is progressing to increase access to clean drinking water and sanitation. There are also some other endocrine disrupting chemicals (EDC) such as disinfection byproducts and pesticides which is more suitable to be extracted from water samples using solid phase microextraction due to low contamination in water. It is very important to research, detect and extract the bisphenol and phthalates from water sources as these pollutants might cause health issues and environmental pollutions which cannot be resolved in future due to its smaller size and its existence in large quantity.